A Hydrochemical Characterization & Quality Assessment of Groundwater and River water at Kaptai-Lichubagan Roadcut Section, Kaptai Upazila, Rangamati Hill District, Bangladesh - Sultana, Sarmin; Rahman, Md Mostafizur; Nawrin, Nazia; Rafiq, Muhammad Risalat; Sakib, Nazmus (The Dhaka University Journal of Earth and Environmental Sciences, 2025)
The people living in the Kaptai-Lichubagan roadcut area of Kaptai Upazila in Rangamati Hill District, Bangladesh, rely on groundwater for drinking. This study aims to investigate the hydrochemistry of groundwater and river water, associated hydrochemical processes and to assess drinking water quality. In total, 26 water samples were collected for laboratory analysis; 22 from groundwater at depths ranging from 9 to 198 meters, and 4 from Karnaphuli river. Both groundwater and river water pH levels suggest acidic to neutral water. Electrical conductivity (EC) values also indicate mostly fresh groundwater and river water, and EC of groundwater varies both spatially and vertically. The total hardness (TH) of groundwater suggests moderately hard to very hard water, whereas the river water is mostly soft. Most groundwater samples are either Ca-Mg-HCO3 type or mixed Ca-Na-HCO3 and Ca-Mg-SO4-Cl type. In contrast, all the river water samples are Ca-Mg-HCO3 type. Groundwater exhibit variable polygonal shapes in stiff diagrams, characterized by relatively low to moderate major ions. However, there is one sample which shows higher cations suggesting anthropogenic influence. River water show similar patterns but smatter shapes characterized by relatively low major ions. Groundwater is primarily influenced by water-rock interaction andsilicate weathering is the dominant controlling factor of groundwater chemistry, followed by carbonate dissolution. Groundwater samples are mostly undersaturated with minerals - calcite, dolomite, gypsum, and siderite, which possess the potential for dissolution. None samples exceed the Bangladesh drinking standard (BDS) for As (50 µg/L). River water is also As safe. While As shows no spatial variability, FeTotal shows significant spatial variability in the study area. Water Quality Index (WQI) indicates about 90% water samples including most groundwater and all river water samples is of excellent quality for consumption Routine monitoring of the water quality in this area is recommended to ensure its continued safety. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(2), 2024, P 31-47